Analysis of social management, knowledge and technological innovation in state entities (2017)
The present Research Essay will deal with issues and definitions related to Social Management, Knowledge, Innovation and Technology in the State Entities. Likewise, the behavior of the entities before each of the mechanisms that externally involve the citizens in the satisfaction of the necessities, their connection and participation in the programs created to solve social problems, and internally to the public officials who count with the knowledge required for the position to be performed, and the necessary tools to fulfill their duties. It should be noted that the important thing for this essay is to observe the compliance of the state entity in its main mission "To satisfy the needs of the citizens, providing the necessary conditions for a better quality of life", also offers the internal officer a working environment Appropriate, with adequate and up-to-date knowledge and technology for the fulfillment of its functions in pursuit of the objectives established by the state entities.